The Concept of Improving the Quality of Slum Areas in the Simarito Area in Simarito Village, West Siantar District, Pematang Siantar City - Umar Juni Dalimunthe; Abdi Sugiarto; Cut Nuraini (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This study aims to research the Concept of Improving the Quality of Slum Areas in the Simarito Area in SimaritoVillage, West Siantar District, Pematang Siantar City. The qualitative research method used is qualitativedescriptive. The descriptive method includes collecting data to test hypotheses or answer questions regardingthe latest status of the research subject. To obtain data that is in accordance with what is needed and on time fortime and material efficiency. Research results on Infrastructure Improvement: The development andimprovement of basic infrastructure, such as roads, drainage, and sanitation systems, has succeeded in improvingthe accessibility and quality of life of the community. Improved Health and Hygiene: Sanitation programs and theprovision of clean water have reduced health problems caused by unclean environments. CommunityParticipation: Community involvement in the planning and implementation of regional rejuvenation has shownpositive results. Improving the Local Economy: Training and support programs for micro enterprises have had apositive impact on the local economy. Environmental Awareness: Environmental awareness and educationcampaigns have succeeded in instilling sustainability values among the community. Stakeholder Collaboration:Cooperation between the government, NGOs, and the private sector has strengthened the implementation ofrejuvenation programs. This synergy allows for more effective and efficient use of resources, as well asaccelerating the process of improving the quality of the region.